Sarcoidosis - Eishi, Yoshinobu (IntechOpen, 2013)
More than 130 years have passed since the first description of sarcoid lesions by Sir Jonathan Hutchinson, but the cause of this systemic granulomatous disease is still unknown. Sarcoidosis remains a somewhat mysterious disease because many patients may enter spontaneous remission but some patients are chronically affected or relapse after intervention. Advances in recent sarcoidosis researches have added new insights to our understanding of complexity of sarcoidosis as introduced in this textbook, which includes a new concept of etiology as an endogenous infection caused by hypersensitivity to indigenous bacteria, updated immunopathogenesis and genetic factors, new directions in therapy, and new diagnostic approaches with EBUS-TBNA and FDG-PET. I believe this textbook is useful not only in practice but also for future researches of sarcoidosis.